Hubungan Pengetahuan, Sikap, dan Perilaku Cuci Tangan Ibu Terhadap Kejadian Diare pada Balita di RSUD dr. Fauziah Bireuen: The Relationship of Mother’s Knowledge, Attitude, and Hand Washing Patterns With The Incident of Diarrhea in Toddler in RSUD dr. Fauziah Bireuen - Laili Purnama; Armiatin, Armiatin; Nasiatul Aisyah Salim (JOHAR (Journal of Hospital Administration Research), 2024)
Introduction: Diarrhea is the second cause of death in children under five years of age. Diarrhea can be treated and prevented by the main caregiver at home, namely the mother. Mothers are the main health service providers so healthy maternal habits can improve children’s health and reduce morbidity. This is because children cannot carry out daily activities. Maternal knowledge and a child’s health are interrelated. The practice of washing hands can reduce the incidence of diarrhea by 35 %. Research objective: to determine the relationship between mother’s knowledge, attitudes, and hand washing behavior and the incidence of diarrhea in toddlers in the children’s room at dr. Fauziah Bireuen Hospital. Research method: This type of research is quantitative research with a cross sectional design. The population is mothers of children suffering from diarrhea in the children’s room at RSUD dr. Fauziah Bireuen as many as 32 people. The sampling technique is total sampling. The data collection technique uses a questionnaire. Data analysis used the chi-square test. Research results: show that there is a relationship between mothers’ knowledge, attitudes and hand washing behavior and the incidence of diarrhea in toddlers in the children’s room at RSUD dr. Fauziah Bireun. Conclusion: to reduce the incidence of diarrhea in toddlers requires knowledge, attitudes, and good hand-washing behavior from mothers.